INSTALLMENT SALES OF REAL ESTATE. - Ross, F. E. (The Accounting Review, 1926)
Abstract Under regulations prescribed by the Commissioner with the approval of the Secretary, a person who regularly sells or otherwise disposes of personal property on the installment plan may return as income there from in any taxable year that proportion of the installment payments actually received in that year which the total profit realized or to be realized when the payment is completed, bears to the total contract price. The solution of the problem is so simple that there would be no excuse to raise a discussion of the subject were it not for the published decisions of responsible revenue officers. Every beginner in accounting understands or should understand the use of suspense and deferred revenue accounts. Accordingly it is not difficult for him to appreciate that what is received in one accounting period may be income of a different period, just as a cost incurred in one period may be an expense in another.